Valori della persona e modelli di tutela contro i rischi ambientali e genotossici Esperienze a confronto - Pernice, Francesco; ALCARO, FRANCESCO; Fenga, Concettina; MOSCATI, Enrico; Tommasini, Raffaele (Proceedings e report, 2008)
This book brings together studies produced during the implementation of the MIUR-PRIN 2005/2007 inter-university project on 'The individual in domestic and community legislation: new models for protection and management of environmental and genotoxic risks'. The managers of the working groups organised itinerant study days in Messina, Florence and Rome, also with a view to in-the-field verification of different experiences and realities. Within the framework of interdisciplinary liaison, the important contributions made by eminent scholars have enabled the in-depth study at legal and medical level of the most appropriate tools for guaranteeing preventive and restrictive mechanisms in relation to protection from the damage of potentially genotoxic environmental, occupational or individual factors. This is the most recent approach to the new code of the environment, utilising the principle of precaution which is intended to induce the jurist and the medical scientist to discern profiles of continuity and discontinuity in the promotion and protection of individual values.